2020
DOI: 10.1002/adts.202000093
|View full text |Cite
|
Sign up to set email alerts
|

Flickering Polarons Extending over Ten Nanometres Mediate Charge Transport in High‐Mobility Organic Crystals

Abstract: Progress in the design of high‐mobility organic semiconductors has been hampered by an incomplete fundamental understanding of the elusive charge carrier dynamics mediating electrical current in these materials. To address this problem, a novel fully atomistic non‐adiabatic molecular dynamics approach termed fragment orbital‐based surface hopping (FOB‐SH) that propagates the electron‐nuclear motion has been further improved and, for the first time, used to calculate the full 2D charge mobility tensor for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(71 citation statements)
references
References 69 publications
3
61
0
Order By: Relevance
“…[ 8–11 ] We have recently shown, using advanced quantum dynamical simulations, that charge carriers in single‐crystalline OS form “flickering polarons,” objects that are half‐way between waves and particles. [ 12–14 ] We found they are delocalized over up to 10–20 molecules in the most conductive crystals and constantly change their shape and extension under the influence of the thermal motion of the atoms (crystal vibrations). [ 12 ] Taking the example of bulk crystalline pentacene, we found that the excess hole is typically delocalized over 17 molecules, [ 12,13 ] in excellent agreement with experimental estimates from electron spin resonance data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 8–11 ] We have recently shown, using advanced quantum dynamical simulations, that charge carriers in single‐crystalline OS form “flickering polarons,” objects that are half‐way between waves and particles. [ 12–14 ] We found they are delocalized over up to 10–20 molecules in the most conductive crystals and constantly change their shape and extension under the influence of the thermal motion of the atoms (crystal vibrations). [ 12 ] Taking the example of bulk crystalline pentacene, we found that the excess hole is typically delocalized over 17 molecules, [ 12,13 ] in excellent agreement with experimental estimates from electron spin resonance data.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12–14 ] We found they are delocalized over up to 10–20 molecules in the most conductive crystals and constantly change their shape and extension under the influence of the thermal motion of the atoms (crystal vibrations). [ 12 ] Taking the example of bulk crystalline pentacene, we found that the excess hole is typically delocalized over 17 molecules, [ 12,13 ] in excellent agreement with experimental estimates from electron spin resonance data. [ 15 ] The computed mobility, of 9.6 cm 2 V −1 s −1 , [ 13 ] is also in good agreement with experiment, 5.6 cm 2 V −1 s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Existing methods can be broadly divided into atomistic ones and those based on effective Hamiltonians. Atomistic calculations track the dynamics of both the nuclear degrees of freedom (usually using molecular mechanics) and the electronic ones (using quantum equations of motion) [31][32][33][34][35][36][37]. Atomistic simulations do not have adjustable parameters, but they suffer from the considerable cost of tracking the atomic motion.…”
mentioning
confidence: 99%
“…1 ps [34][35][36][37]. These capabilities enable remarkable simulations of layered organic crystals, which admit a twodimensional simulation and are ordered enough that mobilities converge rapidly.…”
mentioning
confidence: 99%
“…While beyond the scope of this article, we note that the 2 1 A g – state exhibits a lower transition dipole moment than 1 1 B u + 7 ,. 37 Given that the annihilation cross-section of a state is proportional to its transition dipole moment 38 40 this may explain why the 2 1 A g – symmetry excitons do not exhibit significant annihilation effects. 41 A similar effect has been observed in H- and J-aggregate systems.…”
Section: Resultsmentioning
confidence: 99%